Analisis Kandungan Vitamin C Bahan Makanan dan Minuman dengan Metode Iodimetri - Harefa, Nelius; Feronika, Nella; Kana, Angel Djara; Hutagalung, Romelia; Chaterine, Donna; Bela, Yongkifianus (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2020)
Vitamin C is an essential compound for human. The sources of Vitamin C are very abundant both natural and artificial. In this study, analyzed levels of Vitamin C in natural foods and artificial drinks that can be consumed by humans. The analysis aims to provide information on Vitamin C levels from these foodstuffs and beverages, so that humans can predict the content of Vitamin C that must be consumed or consumed daily. Many methods can be used to determine Vitamin C in a sample, the method used in determining Vitamin C in a research sample is the iodimetric method. Based on the analysis of research data, the Vitamin C level in sample A was 2.286 mg/g sample, the Vitamin C level in sample B was 2.204 mg/g sample, and the Vitamin C level in sample C was 0.044 mg/g sample. The data shows that humans need about 18 - 68 grams of sample A material per day to fulfill 40 - 90 mg of Vitamin C needed. Sample B material is needed around 20 - 70 grams to fulfill 40 - 90 mg of Vitamin C needed. And, the sample C material is needed around 56 - 106 grams per day to fulfill 40 - 90 mg of Vitamin C needed.